Effect of metformin therapy on circulating amino acids in a randomized trial: the CAMERA study: Metabolism - Preiss, D; Rankin, N; Welsh, P; Holman, R; Kangas, A; Soininen, P; Würtz, P; Ala-Korpela, M; Sattar, N (Wiley, 2016)
Aims To investigate whether metformin therapy alters amino acid concentrations, increased levels of which have been found to predict Type 2 diabetes. Methods In the Carotid Atherosclerosis: Metformin for Insulin Resistance (CAMERA) study (NCT00723307), 173 individuals without Type 2 diabetes, but with coronary disease, were randomized to metformin (n=86) or placebo (n=87) for 18 months. Plasma samples, taken every 6 months, were analysed using quantitative nuclear magnetic resonance spectroscopy. Ten metabolites consisting of eight amino acids [three branched-chain (isoleucine, leucine, valine), three aromatic (tyrosine, phenylalanine, histidine) and two other amino acids (alanine, glutamine)], lactate and pyruvate were quantified and analysed using repeated-measures models. On-treatment analyses were conducted to investigate whether amino acid changes were dependent on changes in weight, fat mass or insulin resistance measured using homeostasis model assessment. Results Tyrosine decreased [-6.1 μmol/l (95% CI -8.5, -3.7); P<0.0001], while alanine [42 umol/l (95% CI 25, 59); P<0.0001] increased in the metformin-treated group compared with the placebo-treated group. Decreases in phenylalanine [-2.0 μmol/l (95% CI -3.6, -0.3); P=0.018] and increases in histidine [2.3 μmol/l (95% CI 0.1, 4.6); P=0.045] were also observed in the metformin group, although these changes were less statistically robust. No changes in these four amino acids were accounted for by changes in weight, fat mass or homeostasis model assessment of insulin resistance values. Levels of branched-chain amino acids, glutamine, pyruvate and lactate were not altered by metformin therapy. Conclusions Metformin therapy results in a sustained and specific pattern of changes in aromatic amino acid and alanine concentrations. These changes are independent of any effects on weight and insulin sensitivity. Any causal link to metformin's unexplained cardiometabolic benefit requires further study.